An EPQ model in the perspective of carbon emission reduction. (24th April 2019) - Sinha, Sudipta; Modak, Nikunja Mohan
One of the major reasons behind the abnormal increase of Earth's temperature is the uncontrollable emission of CO2 of production houses. Industrialists are very much interested to enhance their profit only instead of greater interest of the society. The paper develops an economic production quantity (EPQ) model reckoning the aspects of carbon emission and carbon trading. A production house has to pay compulsory tax for carbon emission and incurs a penalty cost for the emission of excess carbon dioxide than its permissible limit. The producer is able to earn revenue by the way of carbon trading by controlling carbon emission within the permissible limit. Plantation of trees can effectively mitigate emission. Numerical examples are given to illustrate the validity of the proposed model and comparison of result between with and without plantation is provided. Comprehensive sensitivity analysis of various parameters has also been carried out.